Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

Check my work please, how to simplify this differentiated function?

Differentiate the following function:

y=( x / (x^2 + 1))^2

I did:

y'= 2(x/(x^2+1) ((x^2+1)(1) - (x)(2x) / ((x^2+1)^2)

y' = 2(x / (x^2+1)) ((x^2+1-2x^2) / ((x^2+1)^2)

Now to simplify this, do I cancel out the (x^2+1) in the second term in the parenthesis? Not sure where to go from here to simplify this down..any help would be really appreciated!

1 Answer

Relevance
  • 7 years ago

    Simplify the function by multiplying the top and bottom by x^2 + 1. The easy way to differentiate the function is to use log. That is:

    ln(y) = 2ln(x/(x^2 + 1))

    ln(y) = 2(ln(x) - ln(x^2 + 1))

    ln(y) = 2ln(x) - 2ln(x^2 + 1)

    Then, by implicit differentiation, we obtain:

    1/y * dy/dx = (2/x) - 2 * 2x/(x^2 + 1)

    dy/dx = y((2/x) - 4x/(x^2 + 1))

    dy/dx = (x/(x^2 + 1))^2 * ((2/x) - 4x/(x^2 + 1))

    dy/dx = 2/(x^2 + 1)^2 - 4x^2/(x^2 + 1)^3

    Hope this helps!

Still have questions? Get your answers by asking now.